Comparative Mass Transfer Study of Basic and Acid Magenta Adsorption onto Natural Clay - Radia Yous; Hakima Cherifi; Razika Khalladi (Indonesian Journal of Chemistry, 2019)
In this work a comparative study of basic and acid magenta sorption on Algerian natural untreated clay was investigated using theoretical models for the following conditions C0(BM) = 200 mg/L, C0(AM) = 150 mg/L, V = 500 mL, CB(BM) = 1g/L, T = 22 °C. Adsorption mechanism of both dyes based on an intraparticle diffusion, external mass transfer, and kinetic models was examined. Statistical error functions regression coefficient (R2), the root mean square error (RMSE) and the average relative error deviation ARED were used to estimate the deviation between experimental and theoretical values. This work indicated that the experimental results obtained for both dyes fitted well the chosen models in the following order: External model of Boyd < Kinetic model < Urano and Tachikawa model < External model of Weber and Morris ≤ Weber and Morris internal diffusion model. However, the calculated values of Biot number are 32.31 and 69.33 for acid magenta and basic magenta respectively, indicating that the adsorption of both dyes onto the same clay is initially controlled by external film diffusion at the first ten minutes. The adsorption capacity of the tested clay for both dyes is remarkable compared to other natural adsorbents. Where the best results were obtained for basic magenta (qexp = 198.028 mg g–1, R2 = 0.992, ARED = 0.128 and RMSE = 0.461).